Mortgage Securitisation-An Investigation of the Risks Inherent in Financing Process: from the borrowers to investors - Wei, Xiaoxu (2008)
Along with the subprime mortgage crisis, the growing rates of default have lead to serious travail for many big financial players, such as Bear Stearns in the U.S., Northern Rock in the U.K. Consequently, many academics argue that the complex securitization process weakens the incentives of the participants to screen and monitor the quality and performance of the loan which make the loans become highly risky. Particularly, the substantial credit risk inherent in the process can lead to losses for each participant within the chain and can result the serious systemic risk to the whole financial sector and thus broader economy. The purpose of this dissertation is to investigate how the risks are transferred and distributed in the mortgage financing process via mortgage securitization as these risks are closely related to the recent crisis caused by subprime mortgages and its related structured instruments. By provide the understanding of both prime mortgage and subprime mortgage lending, the problems about these risks seem not come from the pure innovation of the mortgage securitization; rather the problems arise from the general market failure and the absence of risk control capabilities. Especially, the consequences of the risks are extended and magnified by these problems which led to the carnage of the subprime mortgage market and these are better reflected by the case of Bear Stearns crisis. As a result, there is a strong need to draw regulation and policy implications to practitioners within the financial and economic environment.